2011
DOI: 10.1620/tjem.225.5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Features of Second Primary Malignancies in Head and Neck Cancer Patients in Japan

Abstract: Second primary malignancies (SPMs) are one of the most critical problems in treating head and neck cancer patients. Our hospital had 742 patients with a diagnosis of malignant head and neck tumors during the five-year period from 2002 to 2006. In this study, we analyzed 360 of those patients who were assumed to have risk factors such as alcohol and tobacco use: 106 oral, 120 laryngeal, 50 oropharyngeal and 84 hypopharyngeal cancer patients. Synchronous SPMs are defined as second cancers diagnosed at the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
2
21
1
Order By: Relevance
“…The incidences of synchronous and metachronous SPT in this study were 6.2% (including simultaneous SPT) and 14.8%, respectively. Those were comparable with previous studies, which reported incidences of synchronous SPT that ranged from 3.8% to 7.0% and incidences of metachronous SPT that ranged from 9.0% to 20% . In the current study, all simultaneous SPTs were located inside the oral cavity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidences of synchronous and metachronous SPT in this study were 6.2% (including simultaneous SPT) and 14.8%, respectively. Those were comparable with previous studies, which reported incidences of synchronous SPT that ranged from 3.8% to 7.0% and incidences of metachronous SPT that ranged from 9.0% to 20% . In the current study, all simultaneous SPTs were located inside the oral cavity.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported the rates of second primaries of head and neck squamous cell carcinomas varying from 8% to 21% . A study analyzing patients with laryngeal carcinoma showed a significant reduction of survival rate in patients developing a second primary tumor (SPT) when compared to those without .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recurrences are local (Hakeem et al, 2012;Priya et al, 2012). A considerable proportion of cases (34%) in Japan presented with second primaries (Shiga et al, 2011). The clinicopathological factors that influence the treatment outcome and likelihood of recurrence are use of tobacco, advanced T stage or stage III-IV disease at diagnosis, including local regional nodal involvement, positive resection margins or the resection margins being very close to the tumour and thickness of tumour ≥7mm (Battoo et al, 2012;Hakeem et al, 2012;Priya et al, 2012;Wang et al, 2012).…”
Section: Recurrencementioning
confidence: 99%
“…Those studies have reported that the prognosis of patients with synchronous cancers is significantly lower than that of patients with metachronous cancers, and that second primary malignancies in the esophagus or lung contribute to a poorer outcome relative to other types. This suggests that the decline in survival rates in patients with SPTs is due to high morbidity requiring multiple surgeries, lack of well-established treatment in managing multifocal oral cancers, restricted therapeutic options, and relevant habits of the patient1920.…”
Section: Discussionmentioning
confidence: 99%